In Vitro Evaluation of Different Approaches and Dissolution Enhancement Technique of Poorly Water-Soluble Drug Ibuprofen - Hossain, ASM Monjur Al; Dutta, Konika Rani; Hossain, Md Lokman (Dhaka University Journal of Science, 2016)
Ibuprofen Solid Dispersion (SD) was prepared by simple Physical Mixing (PM) and Kneading Method (KM). In these two cases, four polymers named poloxamer 407, sodium carboxy methyl cellulose, croscarmellose sodium and pregelatinized starch were used to enhance the dissolution profile of Ibuprofen. In both methods, the ratio of drug and carrier were 1:1, 1:2, 1:3 of which the ratio of 1:3 in KM gave comparatively better result than PM method. In vitro dissolution study was performed in distilled water in 50 rpm and at 37 ± 0.5°C. In case of pure Ibuprofen, dissolution rate was only 26% after 60 minutes (mins) of dissolution. While in KM, Ibuprofen pregelatinized starch formulation at 1:3 ratio showed better dissolution rate. After 60 mins, dissolution rate of Ibuprofen was 72%. The SD formulations of Ibuprofen-pregelatinized starch and Ibuprofen-Na-CMC of physical mixing and kneading techniques (1:3 ratio) were characterized by Fourier Transform Infrared Spectroscopy (FTIR). Dhaka Univ. J. Sci. 64(2): 169-175, 2016 (July)